Analisis Efektivitas Dan Kontribusi Pajak Penerangan Jalan Dalam Meningkatkan Pendapatan Asli Daerah Di Kabupaten Sikka Tahun 2018-2022 - Hermanus Yosep Kader; Petrus Da Silva; Elisabet Luju (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This research was grounded on the issue of poor realization of local revenue in Sikka regency despite being supported by street lighting tax. Therefore, this study aimed to (1) determine the level of effectiveness of the street lighting tax. (2) to determine the level of contribution of street lighting in an effort to increase local revenue. The population in this study was the Regional Revenue Agency (BAPENDA) of Sikka regency. Data were collected through documentation and analysed using effectiveness analysis and contribution analysis methods. The result of this study indicated that the level of effectiveness of street lighting tax in 2018-2022 fluctuated with an average of 106,06% where these results fall into the highly effective category. In 2018-2020, the level of effectiveness revenue was in the highly effective category. Meanwhile, in 2021 and 2022, the level of effectiveness of street lighting tax was in the effective category. The contribution of street lighting tax in increasing regional own-source (PAD) in 2018-2022 fluctuated and was included in the very less category with an average percentage of 7.89%.